Strategies of conquest The politics of Berberisation (its pillars, ways and means, dimensions) - aguibi, Ezz El-Din (The Algerian Historical Journal, 2026)
The Muslim conquerors relied on several strategies to achieve the goal of spreading Islam in the horizons, and the policy of uniting the peoples who had recently converted to Islam was one of the most important of these strategies, which was implemented by the Prophet (PBUH) and the Rightly-Guided Caliphs after him, and then followed by the Muslim conquerors after them, including the leaders of the Islamic conquest in the Maghreb, who based their spread of Islam on the policy of uniting the Berbers, the inhabitants of the country, to bring them to the side of Islam and spread it among them. This policy had pillars and principles stemming from what the religion of Islam and its laws recommended, and they adopted many means and methods for this purpose, which had a good effect on the Berbers’ interaction with the Muslim conquerors, and their conviction of the message of Islam to the point that they began to place themselves as a torch in order to spread its lights and guidance. Therefore, this study attempts to shed light on the roots of this policy and its principles, its means and methods, and finally its dimensions in the countries and people, which the Muslim conquerors implemented with the Berbers to unite them.